(untitled) (Revista Contexto & Saúde, 2025)
This study aimed to evaluate the relationship between eating behaviors during pregnancy and infant birth weight. This was a cross-sectional study conducted with pregnant women receiving care in public and private health services in Lavras, Minas Gerais, Brazil. Eating behavior was assessed using the Three Factor Eating Questionnaire (TFEQ), the Intuitive Eating Scale-2 (IES), and the Mindful Eating Questionnaire (MEQ). Infant birth weight was reported by the mother, based on data recorded in the Child Health Booklet. The Shapiro-Wilk test was performed to check for normality, and Spearman’s correlation and Mann-Whitney U tests were applied to correlate and compare different domains of eating behavior with infant birth weight. The sample consisted of 127 mother-child pairs, with maternal age ranging from 18 to 42 years and gestational age at birth between 37 and 42 weeks. No correlations or associations were found between different eating behaviors during pregnancy and infant birth weight. Intuitive and mindful eating behaviors adopted during pregnancy, when considered in isolation, may not be able to predict deviations in infant birth weight.